CURRICULUM ANALYSIS OF THE INTEGRATED ISLAMIC SCHOOL NETWORK (JSIT) AT AL-FITYAN SCHOOL MEDAN ISLAMIC ELEMENTARY SCHOOL - Wahyu Hidayat; Sugiharto Sugiharto; Wildansyah Lubis (Sensei International Journal of Education and Linguistic, 2021)
This study aims to determine the standards of the JSIT curriculum implemented in SDIT Al-Fityan School Medan, especially in the Graduate Competency Standards (SKL), coaching standards, and cooperation standards. These educational standards are the superior standards used in Integrated Islam-based (IT) schools which are commonly called IT schools with the central and regional administrations of JSIT (Integrated Islamic School Network), all IT-based schools are of course Islamic and Islamic based so that they are created. JSIT container for each region to develop and add the character of Islamic education, especially to the JSIT curriculum. This type of research uses qualitative research, namely descriptive analysis, in which this research uses research that is full of theory and expert analysis. The data analyzed were the results of interviews, observations, and documents using photo evidence. The data analysis stage was carried out, namely data reduction, data presentation, conclusion, and data verification. The results showed that the implementation of educational standards, especially in graduate competency standards, coaching standards, and cooperation standards adopted by SDIT Al-Fityan School Medan. On the standard of graduate competence, SDIT Al-Fityan School Medan emphasized that students who have finished from the school must be able to call to prayer, iqomah (for male students), night prayer (Qiyamul Lail), fardhu prayer, sunnah prayer, can distinguish between which is good and which is bad, not afraid of spirits, the target of memorizing 10-15 Juz Al-Qur'an is completed from SDIT Al-Fityan School Medan.